Co-infection by Mycobacterium Tuberculosis And Klebsiella Pneumoniae in an Elderly Male With Multiple Co-morbidities: A Rare Entity With High Mortality - Hossain, Homayra Tahseen; Noor, Nawsabah; Akhter, Sharmin; Ahmed, Mohiuddin; Islam, Quazi Tarikul (Bangladesh Journal of Medicine, 2022)
Klebsiella pneumoniae and Mycobacterium tuberculosis coinfection is one of the most lethal combinations with high mortality specially if there is delay in diagnosis and proper management. Patients with uncontrolled diabetes mellitus are prone to develop this type of serious infection.There is a considerable overlap in the clinical presentation of these critical pulmonary infections hence there is need for a high index of clinical suspicion, appropriate judicious investigations, and promt management to improve survivality. Here, we have presented Mycobacterium tuberculosis and Klebsiella pneumonia co-infection presenting as cough, chest pain, and shortness of breath in an elderly male with multiple co-morbidities, like uncontrolled diabetes mellitus, hypertension, prosthetic aortic valve in situ (for aortic stenosis)& previous history of ishchaemic stroke. This combination is rare and to the best of our knowledge not reported in the literature from Bangladesh. Bangladesh J Medicine 2022; 33: 52-57